Effects of an Azolla–Spirulina Green Concentrate on the Performance, Physiological Status, and Egg Lipid Profile of Japanese Quail - Kusuma, Satria Budi; Wulandari, Suci; Respati, Adib Norma; Siswantoro, Dharwin; Bahariawan, Amal (Jurnal Ilmu-Ilmu Peternakan, 2026)
This study aimed to evaluate the effects of a “green concentrate” based on Azolla pinnata and Spirulina sp. on the production performance, haematological profile, physiological status, and egg lipid quality of Japanese quail (Coturnix coturnix japonica). A completely randomized design (CRD) was applied using 54 laying quails assigned to three dietary treatments: T0 (basal diet), T1 (basal diet + 10% Azolla pinnata), and T2 (basal diet + 10% Azolla pinnata + 0.1% Spirulina sp.), with six replicates per treatment. The parameters observed included production performance (egg production, egg weight, feed intake, and feed conversion ratio), haematological profile (erythrocyte, haemoglobin, haematocrit, and differential leukocyte), relative organ weight, and the egg lipid profile (cholesterol and fatty acids). The results revealed that the dietary treatments had no significant effect (P>0.05) on production performance or haematological parameters, indicating that physiological homeostasis and health status were maintained. However, numerical improvements in gizzard development and reduced liver weight were observed, suggesting the occurrence of adaptive metabolic responses. Importantly, the quality of the eggs significantly improved, as indicated by reduced yolk cholesterol and increased docosahexaenoic acid (DHA) levels in the T1 and T2 treatments. In conclusion, the inclusion of 10% Azolla pinnata combined with 0.1% Spirulina sp. can be considered a safe and effective feeding strategy to produce functional quail with improved lipid profiles without compromising performance or physiological stability